Cancer prevention policy in the EU: Best practices are now well recognised; no reason for countries to lag behind. (December 2018) - Espina, Carolina; Soerjomataram, Isabelle; Forman, David; Martín-Moreno, Jose M.
Highlights: National Cancer Control Programmes (NCCPs) are key elements in cancer control. NCCPs' role in national cancer policies of EU countries has grown significantly. Few quantitative assessments are available to evaluate success or failure of the implementation of NCCPs. Research on methodologies to better assess the effectiveness of cancer prevention policies should be enhanced. Abstract: Through the application of science to public health practice, National Cancer Control Programmes provide the framework for the development of policies on cancer control, with the ultimate goal of reducing cancer morbidity and mortality, and improving quality of life. In the last decade, a substantial number of Member States in the European Union (EU) have formulated and/or updated their National Cancer Control Programmes, Plans or Strategies including primary prevention (health promotion and environmental protection), secondary prevention (screening and early detection), integrated care and organization of services, and palliative care as main elements. Although tobacco control and population-based screening policies are examples of best practices that are gradually being implemented in most of the EU countries, there are still large regional differences in cancer burden arising from the wide variety of social determinants and other epidemiological factors, along with gaps in the policy and practical articulation of cancer control within the health systems. On the other hand, few quantitative assessments are available with regard to evaluating the success or failure of the implementation of these programmes, especially in terms of reducing cancer incidence or mortality. An EU framework to better assess of the effectiveness of cancer prevention policies and the factors triggering shortfall in best practices implementation seems imperative.